Effects of Ionizing radiation on Cardiac Implantable Electronic Devices (CIEDs) in patients with esophageal cancer undergoing radiotherapy: a pilot study - Uzun, Davut D.; Salatzki, Janek; Xynogalos, Panagiotis; Frey, Norbert; Debus, Jürgen; Uzun-Lang, Kristin (Cancers, 2024)
(1) Background: The prevalence of cancer patients relying on cardiac implantable electronic device (CIED) is steadily rising. The aim of this study was to evaluate RT-related malfunctions of CIEDs. (2) Methods: We retrospectively analyze sixteen patients with esophageal cancer who were treated with radiotherapy between 2012 and 2022 at the University Hospital Heidelberg. All patients underwent systemic evaluation including pre-therapeutic cardiological examinations of the CIED functionality and after every single irradiation. (3) Results: Sixteen patients, predominantly male (14) with a mean age of 77 (range: 56-85) years were enrolled. All patients received 28 fractions of radiotherapy with a cumulative total dose 58.8 Gy. The mean maximum dose at the CIEDs was 1.8 Gy. Following radiotherapy and during the one-year post-radiation follow-up period, there were no registered events associated with the treatment in this evaluation. (4) Conclusion: The study did not observe any severe CIED malfunctions following each radiation fraction or after completion of RT. Strict selection of photon energy and alignment with manufacturer-recommended dose limits appear to be important. Our study showed no major differences in the measured values of the pacing threshold, sensing threshold and lead impedance after RT.